Correction: Synthesis of Z-alkenes via visible light promoted photocatalytic E → Z isomerization under metal-free conditions. Issue 99 (1st December 2017) - Cai, Wenbin; Fan, Huaqiang; Ding, Dazhong; Zhang, Yongqiang; Wang, Wei
Abstract : Correction for 'Synthesis of Z -alkenes via visible light promoted photocatalytic E → Z isomerization under metal-free conditions' by Wenbin Cai et al., Chem. Commun., 2017, DOI: ; Web:10.1039/c7cc07984b .